Internal and External Conflict of the main characters in the short stories Tuhan, Pawang Hujan, dan Petarung yang Remis by A.S Laksana - Eva nurmayani (Tinta Emas Publisher, 2024)
This research aims to describe the internal conflict and external conflict of the main character named Alit in the short stories Tuhan, Pawang Hujan, dan Petarung yang Remis by A.S Laksana. Alit works as a magician and rain charmer. This research uses descriptive qualitative methods. The data collection technique in this research uses library techniques. Based on the data collection technique used, the data is analyzed using descriptive analysis. The steps in analyzing the data are as follows: Grouping the data based on data type, Reducing data from the data corpus according to the problem being studied, Describing the data to make it clearer. easy to understand, Analyzing data based on predetermined formulas and drawing conclusions. Based on the results of the analysis of the short stories Tuhan, Pawang Hujan, dan Petarung yang Remis by A.S Laksana. There are internal conflicts and external conflicts. Internal conflict is a problem or event that occurs to Alit because of an inner struggle with himself caused by the emergence of desires or feelings that arise from within the character. External conflict in the short stories Tuhan, Pawang Hujan, dan Petarung yang Remis by A.S Laksana, is an event that arises due to the involvement of other people or influences from outside the characters which give rise to feelings of happiness, sadness, disappointment, anger and revenge. This is a description of events that often occur in real life when living in the real world.